Pelatihan Pembuatan Pupuk Biosaka, Upaya Perlindungan Tanaman Berbasis Ekologi Untuk Menjaga Kelestarian Lingkungan - Saryanto Saryanto; Rejo Kirono; Khotim Hanifudin Najib; Ahdan Aufa Ilman; Ainun Jaria; Devi Rahmaningtias; Madiasta Madiasta; Margaretha Eltris Don; Nurul Nur Amelia; Heri Winarno; Lono Madyo (Lembaga Pengembangan Kinerja Dosen, 2024)
Biosaka fertilizer production training is an educational program designed to provide practical knowledge and skills in the production of organic fertilizer through fermentation of natural ingredients. Biosaccharine fertilizer, which is made from plant residues, animal waste and certain microorganisms, offers an environmentally friendly and efficient solution for improving soil fertility and plant health. This training includes an introduction to materials and tools, the fermentation process, and the application of biosaccharide fertilizer to various types of plants. Through this approach, participants—including farmers, agricultural extension workers, and other individuals—are expected to be able to produce high-quality biochemical fertilizer independently. It is hoped that the results of this training will reduce dependence on chemical fertilizers and support sustainable agricultural practices that are more economical and environmentally friendly.